The influence of a GT repeat polymorphism on poly(I:C) induction of the grouper MxII gene promoter in GK cells. Issue 101 (June 2020) - Vo, Thi Tuyet Minh; Lai, Ying-Yi; Lin, Cheng-Hui
Abstract: Interferons play an important role in the fish innate immune system against viral infection by inducing the interferon stimulated genes, such as Mx gene. We cloned the MxII gene promoter from orange-spotted grouper and found three MxII gene promoters. All of them contained two interferon stimulated response elements (ISREs), and three dinucleotide repeat sequences located at 5' end of ISREs. Interestingly, there is a polymorphic GT repeat element located upstream of these ISREs. The three MxII gene promoters respectively contained 27, 29, and 31 GT repeats, namely EcMx_27, EcMx_29, and EcMx_31. To determine whether GT repeat element influence the MxII gene expression, the MxII gene promoters were subcloned into promoterless reporter plasmid and transfected into grouper kidney (GK) cells. The results showed that a significant induction by poly(I:C) was detected in GK cells transfected with pEcMx_31 (2.65 folds) whereas there was no induction in GK cells transfected with pEcMx_27 and pEcMx_29. However, the significant induction by nervous necrosis virus (NNV) infection was found in GK cells separately transfected with three reporter plasmids. These results suggest that the GT repeat element plays an important role in modulation of MxII gene expression and the induction by poly(I:C) and NNV may be mediated through different signal transduction pathways. Highlights: There is a polymorphic GT repeat element located upstream of ISREs in MxII gene promoter. There are at least three kinds of grouper MxII gene promoter containing the various length of GT repeat. GT repeat polymorphisms play an important role in regulating the induction of MxII gene expression. The induction of MxII gene expression by poly(I:C) and NNV may be mediated through different signal transduction pathways.